Syed Husin Ali: Memoirs of a Political Struggle, Syed Husin Ali. Selangor, Malaysia: Strategic Information and Research Development (SIRD), 2012, 273 pages. ISBN: 9789675832499 - Viswanathan Selvaratnam (Kajian Malaysia, 2015)
The review is a critical analysis of Syed Husin Ali's memoirs, a former University of Malaya academic, a public intellectual, a political activist and currently a second-term Senator at the Dewan Rakyat, entitled Memoirs of a Political Struggle. Biographies and memoirs can be valuable political and historical narratives that raise critical economic, political and social issues. They can unlock and fill the lacunae that may exist in our political, economic, social and historical knowledge of the country as well as the individual's representation of the cross-section of his on-going experience in society. Therefore, some do highlight issues that are generally not in the public domain.